Pathomorphological Investigation on Membranous Tracheitis in an Adult Buffalo - Mandeep,; Chandrate, Gauri; Lather, Deepika; Rajesh,; Gupta, Renu (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Membranous tracheitis is an important pathological condition affecting the trachea in animals, usually associated with immunosuppression. This report describes the pathological findings associated with diphtheric tracheitis in an immunocompromised adult buffalo. A carcass of an adult buffalo, with a history of dyspnea, and a large amount of reddish foam flowing from the mouth and nose, presented for necropsy. Detailed postmortem examination was conducted and representative tissue samples were collected for bacteriological isolation and histopathological examination. Macroscopic examination revealed whitish, pale or red coloured blood mixed heavy froth in lumen of trachea with a tightly adhered greenish colour diphtheritic membrane to mucosa. Lungs showed, circular to irregular shaped blackish suffusions, consolidation, along with thin layer of fibrin covering all the lobes. Microscopic examination revealed fibrinous tracheitis and serofibrinous pneumonia in lungs. Mediastinal lymphnode showed severe lymphoid depletion. Bacteriological isolation from tracheal swab and lungs confirmed the presence of Escherichia coli using VITEK 2 system indicating its role in pathogenesis of diphtheritic membrane formation in presence of immunosupression.
Keywords: Buffalo; Diphtheritic membran; E. coli; Necropsy; Trachea